The effectiveness of ethnopedagogy in revitalising local wisdom in formal education: A phenomenological review - Uswatun; Baiq Desi Milandari; Arpan Islami Bilal; Malami Muhammad Garba; Muhammad Hafeez (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Ethnopedagogy is an educational approach grounded in culture that plays an important role in preserving local wisdom amid the challenges of globalisation. This study aims to describe the integration of local cultural values into the learning process and culture-based school programmes, explain the role of ethnopedagogy in shaping students' character and strengthening their cultural identity, and identify forms of collaboration between schools and communities to support the sustainability of local wisdom-based learning. This study used a qualitative phenomenological approach and was conducted at one of the public elementary schools in West Lombok Regency. The research subjects included the principal, teachers, community leaders, and 30 students in grades V and VI. Data was obtained through observation, interviews, and documentation, then analysed using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that ethnopedagogy is effective through Cultural Saturday activities, batik making, and Gendang Beleq drumming, which instil character values and a sense of cultural pride. The incorporation of local wisdom into Civics and Science lessons increases student motivation and understanding, while cooperation between schools and the community supports the sustainability of culture-oriented learning. A comparative analysis of informants' perspectives reveals heterogeneous learning experiences: male students are more interested in traditional Gendang Beleq music, while female students are more interested in batik and dance activities. Ethnopedagogy can be an effective educational approach for strengthening character education, preserving local culture, and developing contextual learning rooted in national cultural values.